Class Difference and the Reformation of Ontario Public Hospitals, 1900-1935: "Make Every Effort to Satisfy the Tastes of the Well-to-Do." - Wishart, James M. (Labour / Le Travail, 2001)
At the beginning of the 20th century, charity hospital governors in Ontario began to explore the possibility of admitting paying patients to help offset the costs of providing medical charity. This transformation entailed changes in administration, as well as concerted publicity and marketing campaigns to rehabilitate the image of the hospital and to attract affluent health consumers. The subsequent construction of new hospital facilities, exclusively for the use of paying customers, was informed by an ideology that mandated the physical separation of social classes and the identification of deserving and less deserving recipients of health care services. This paper examines aspects of the design, management, marketing, and staffing of a number of southern Ontario public hospitals to illustrate how the transformation of these institutions in the years between 1900-1935 actively shaped class inequality within and outside their walls.